Analisis Operasional dan Studi Kelayakan Finansial Pada Proyek Pembangunan Bandar Udara Internasional Dhoho Kediri Melalui Skema KPBU - Zain Zainuddin; Hani Hasanah; Aisyah Ratnasari (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The construction of an airport project must take into account several factors, including financial and operational feasibility. There is its own uniqueness in the construction of Dhoho International Airport – Kediri. This development is the first project built by the national private sector PT Gudang Garam Tbk, through its subsidiary PT Surya Dhoho Investama, with the Government and Business Entity Cooperation (KPBU) scheme where this project is a Green Field Project – Unsolicited. This study aims to determine the financial feasibility and operational analysis. The financial feasibility study is reviewed from cash flow and then analyzed using the Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR), and Payback Period (PP) methods. Operational analysis to plan and determine the investment value needed for the construction of Dhoho International Airport - Kediri. The financial feasibility analysis test uses the Net Present Value (NPV) method worth Rp.559,887,494.00. The Benefit Cost Ratio method obtained a value of 1.0748. The Internal Rate of Return method obtained a value of 14.64%. The Return On Investment capital using the Payback Period method is obtained in 26 years. From the results of the financial feasibility analysis, it can be concluded that the construction of Dhoho International Airport-Kediri has been equipped with Custom, Immigration and Quarantine (CIQ) facilities. Operational tests have been running, especially for domestic flights, followed by Umrah flights.